Current attitudes of teachers towards professional development (a case study in Kelantan) / Ng Siew Foen, Norhaini Mat Lajis and Mohd Zahari Yusoff - Ng, Siew Foen; Mat Lajis, Norhaini; Yusoff, Mohd Zahari (2004)
The development of a nation very much depends on its workforce. And whatever workforce that is available to a country is the product of that country's education system. An integral part of that system is the teachers who are the implementers of whatever educational policy that the country has decided upon. Thus, it is the teachers who mould and shape the workforce who will be responsible for building up the nation. As such, it is vitally important for a country harbouring great ambitions of becoming a developed and progressive nation, such as Malaysia, to ensure that teachers are not only equipped with the right knowledge and skills, but also the right attitude as life-long learners, to enable them to mould and shape a work-force with the right cutting-edge. This study attempts to identify whether the teachers of Kelantan do have such attitude. The attitude level of the teachers were measured based on a set of questionnaires of 24 items. The demographic variables such as gender, years of teaching experience, subject taught and the respondents' educational level, were used to determine whether there are any significant differences between these variables and the attitudes of teachers towards professional development. The Independent T-test and ANOVA were used for the hypotheses testing. The results were, out of six hypotheses, two were rejected. Four factors namely : relevancy of the professional courses, needs of the teachers, support from principal and peers, and both extrinsic and intrinsic motivation were derived from the factorial analysis. Pearson r was used to determine whether there is a significant relationship between these factors and the attitudes of teachers towards professional development. Factor related to motivation was found to have the highest correlation with the level of attitude followed by relevancy, support and needs.